Literasi Keuangan Sebagai Keputusan Investasi: Studi Literature Review: Literasi Keuangan Sebagai Keputusan Investasi: Studi Literature Review - Budiarti, Rindu Reza; Trisnaningsih, Sri (Yayasan Penelitian dan Pengabdian Masyarakat Sisi indonesia, 2025)
Indonesians' interest in investing has increased significantly in recent years. However, the lack of a national financial literacy level that has not yet reached 50% raises concerns about the quality of investment decisions, especially among teenagers. This research examines the relationship between financial literacy and investment decisions based on previous studies. The authors used a literature study approach, analyzing 17 relevant scientific articles published from 2020 to 2024. The results showed that most studies found a positive and significant relationship between financial literacy and the quality of investment decisions. Individuals who are highly financially literate tend to make investment decisions that are rational varied, and in line with their long-term financial goals